Expression and analysis of the glycosylation properties of recombinant human erythropoietin expressed in Pichia pastoris - Teh, Ser Huy; Fong, Mun Yik; Mohamed, Zulqarnain (Sociedade Brasileira de Genética, 2011)
The Pichia pastoris expression system was used to produce recombinant human erythropoietin, a protein synthesized by the adult kidney and responsible for the regulation of red blood cell production. The entire recombinant human erythropoietin (rhEPO) gene was constructed using the Splicing by Overlap Extension by PCR (SOE-PCR) technique, cloned and expressed through the secretory pathway of the Pichia expression system. Recombinant erythropoietin was successfully expressed in P. pastoris. The estimated molecular mass of the expressed protein ranged from 32 kDa to 75 kDa, with the variation in size being attributed to the presence of rhEPO glycosylation analogs. A crude functional analysis of the soluble proteins showed that all of the forms were active in vivo.